Absence of Flair Hyperintense Vessel Sign in Internal Carotid Artery Occlusion: A case report and systematic literature review - Adi Kuncoro; Ahmad Sobri Muda; Mah, Sin Yeat; Anas Tharek; Hanif bin Amran; Nurain Mahfar; Noor Hayatul Al Akmal Noralam (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Large vessel occlusions (LVOs) are commonly associated with distinct pathognomonic radiological features, one of which is the fluid attenuation inversion recovery (FLAIR) hyperintense vessel sign (FHVS). This sign is indicative of an alteration in blood flow dynamics within the affected artery. In the majority of cases, the presence of arterial occlusion is accompanied by FHVS. However, there are exceptions wherein FHVS is absent despite the presence of an occlusion. This case report presents a patient with a complete right internal carotid artery (ICA) occlusion who exhibited relatively mild clinical deficits and limited infarction volume, alongside a notable absence of FHVS. This finding offers an opportunity to explore the pathophysiological mechanisms that might explain the absence of FHVS in such cases and its potential relationship with collateral circulation. The case report is followed by a systematic literature review that supports the phenomenon, that is, the absence of FHVS in cases of internal carotid artery occlusion.